2003
DOI: 10.1097/01.inf.0000078355.29647.d0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral administration of tormentil root extract (Potentilla tormentilla) on rotavirus diarrhea in children: a randomized, double blind, controlled trial

Abstract: The administration of tormentil root extract in controlled doses shortened the duration of rotavirus diarrhea and decreased the requirement for rehydration solutions. Tormentil root extract appears to be an effective measure to treat rotavirus diarrhea in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 12 publications
0
32
0
4
Order By: Relevance
“…Research on developing new ORS that would decrease the volume of loose stools is ongoing. Probiotics and other natural products that may have an effect on shortening episodes of acute infectious diarrhea are being studied [51,52]. Finally, prevention of diarrheal diseases by immunization is desirable.…”
Section: Future Improvements In Diarrhea Management and Preventionmentioning
confidence: 99%
“…Research on developing new ORS that would decrease the volume of loose stools is ongoing. Probiotics and other natural products that may have an effect on shortening episodes of acute infectious diarrhea are being studied [51,52]. Finally, prevention of diarrheal diseases by immunization is desirable.…”
Section: Future Improvements In Diarrhea Management and Preventionmentioning
confidence: 99%
“…In a randomized, double blinded, placebo-controlled clinical trial Russian authors (Subbotina et al, 2003) have shown a high efficacy of a Potentilla erecta rhizome dry extract (one part of dried root with 10 parts of 40% ethanol, 30-40% of tannins, saponin and other components) in child diarrhoea therapy due to a Rotavirus infection (Subbotina et al, 2003). Forty children (20 verum-and 20 placebo-treated) were enrolled.…”
Section: Clinical Studymentioning
confidence: 99%
“…In parallel pharmacological (in vitro and in vivo) evaluations of Potentilla species and their extracts were put forward especially since the 1980s. Within the last years first clinical studies were performed for Potentilla erecta rhizome extracts for the treatment of colitis ulcerosa (Huber et al, 2007) and also for the treatment of virus-induced diarrhoea in children (Subbotina et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Experienced anthroposophic pediatricians recommended this remedy for children suffering from rotavirus enteritis [28]. A shortening of duration and a decrease of rehydration solution requirements in children with rotavirus diarrhea was also demonstrated in a randomized, double-blinded, placebo-controlled trial encompassing 40 patients [51] (table 4). …”
Section: Resultsmentioning
confidence: 99%